Oppositions and alliances between ICCAT contracting parties through an analysis of co-sponsorship of management recommendations - Daniel Gaertner; Nastassia Reyes (Marine Policy, 2025)

Trends and drivers of French tropical tuna purse-seine vessel behavior in the Atlantic and Indian Oceans, 2004–2020 - Wencheng Lau-Medrano; Daniel Gaertner; Francis Marsac; David M. Kaplan (Fisheries Research, 2025)

Spatiotemporal Hotspots of Juvenile Bigeye and Yellowfin Tuna Catches Under Drifting Fish‐Aggregating Devices in the Eastern Atlantic Ocean to Define Moratorium Strata - Sosthene Alban Valeryn Akia; Loreleï Guéry; Pedro J. Pascual‐Alayón; Daniel Gaertner (Fisheries Management and Ecology, 2025)
To reduce catches of juvenile bigeye and yellowfin tuna, while maintaining skipjack catches under drifting fish aggregating devices (dFAD), we analyzed spatiotemporal distributions of dFAD catches by European purse seiners in the Eastern Atlantic Ocean during 1996–2019. To detect hotspots of juvenile dFAD catches, we: identified periods of maximum abundance using a seasonal sub‐series diagram; normalized monthly FAD catches per unit effort; and used emerging hotspots analysis on spatiotemporal density. Two main spatiotemporal strata were identified in the Guinean Gulf, which could be used to establish moratoria on dFAD fishing. These spatiotemporal strata differed from the existing ICCAT moratorium, which spanned a larger part of the African coast. Our findings also indicated that time‐area closures of dFAD‐fishing lasting 3–4 months in smaller areas could be more effective than the current dFAD moratorium to reduce unwanted bycatch in the Eastern Atlantic region. The two metrics we developed for comparison provided clear and measurable evidence that demonstrated how strategic and data‐informed moratoriums can lead to substantial improvements in conservation.

The challenge of assessing the effects of drifting fish aggregating devices on the behaviour and biology of tropical tuna - Amaël Dupaix; Frédéric Ménard; John D. Filmalter; Yannick Baidai; Nathalie Bodin; Manuela Capello; Emmanuel Chassot; Hervé Demarcq; Jean‐Louis Deneubourg; Alain Fonteneau; Fabien Forget; Francesca Forrestal; et al. (Fish and Fisheries, 2024)
Fishers have intensively used drifting fish aggregating devices (DFADs) over the last three decades to facilitate their catch of tropical tunas. DFADs increase purse‐seine efficiency, potentially increasing tuna fishing mortality. They could also have impacts on tuna natural mortality and reproductive potential, and assessing the consequences of their presence at sea on tuna populations is a challenge. The use of DFADs results in a major increase in the number of floating objects, which are spatially heterogeneous at sea. To date, no converging scientific results exist regarding the effects of DFADs on the large‐scale movements and behaviour of tuna, mainly due to the difficulty of disentangling the respective roles of DFADs and environmental factors. Some biological indices show that tuna condition is lower when associated to a floating object than in a free‐swimming school. However, it is not clear whether this is the cause or the consequence of the association nor if it has long‐term effects on individuals' fitness. Further scientific progress requires (i) the collection of time series of indicators to monitor habitat change, individual behaviour, individual fitness, and population dynamics and (ii) experimental studies to identify the underlying behavioural and biological processes involved in associative behaviour. The extent of the modification of the surface habitat by the massive deployment of DFADs and the current uncertainty of the possible long‐term consequences on the individual fitness and dynamics of tuna populations argue for the need for increased awareness of this issue by Regional Fisheries Management Organisations regulating tuna fishing.

Which birds are Brazilians seeing on urban and non-urban feeders? An analysis based on a collective online birding - Eduardo Roberto Alexandrino; Thaís Abreu Camboim; Flávia Guimarães Chaves; Alex Augusto Abreu Bovo; Marco Aurélio Galvão da Silva; Daniela Alves Maia da Silva; Margi Moss; Tatiana Pongiluppi Souza; Clarissa de Oliveira Santos; Caio Bezerra de Mattos Brito; Maristela Camolesi Alcantara; Karlla V. C. Barbosa; et al. (Ornithology Research, 2022)

Catch and bycatch captured by tropical tuna purse-seine fishery in whale and whale shark associated sets: comparison with free school and FAD sets - Lauriane Escalle; Daniel Gaertner; Pierre Chavance; Hilario Murua; Monique Simier; Pedro Jose Pascual-Alayón; Frédéric Ménard; Jon Ruiz; Francisco Abascal; Bastien Mérigot (Biodiversity and Conservation, 2019)

Adaptive responses of tropical tuna purse-seiners under temporal regulations - Edgar Torres-Irineo; Michel Dreyfus-León; Daniel Gaertner; Silvia Salas; Paul Marchal (Ambio, 2017)

Consequences of fishing moratoria on catch and bycatch: the case of tropical tuna purse-seiners and whale and whale shark associated sets - Lauriane Escalle; Daniel Gaertner; Pierre Chavance; Alicia Delgado de Molina; Javier Ariz; Bastien Merigot (Biodiversity and Conservation, 2016)

Environmental factors and megafauna spatio‐temporal co‐occurrence with purse‐seine fisheries - Lauriane Escalle; Maria Grazia Pennino; Daniel Gaertner; Pierre Chavance; Alicia Delgado de Molina; Hervé Demarcq; Evgeny Romanov; Bastien Merigot (Fisheries Oceanography, 2016)
Tropical tuna purse‐seine fisheries spatially co‐occur with various megafauna species, such as whale sharks, dolphins and baleen whales in all oceans of the world. Here, we analyzed a 10‐year (2002–2011) dataset from logbooks of European tropical tuna purse‐seine vessels operating in the tropical Eastern Atlantic and Western Indian Oceans, with the aim of identifying the principle environmental variables under which such co‐occurrence appear. We applied a Delta‐model approach using Generalized Additive Models ( GAM ) and Boosted Regression Trees ( BRT ) models, accounting for spatial autocorrelation using a contiguity matrix based on a residuals autocovariate ( RAC ) approach. The variables that contributed most in the models were chlorophyll‐a concentration in the Atlantic Ocean, as well as depth and monsoon in the Indian Ocean. High co‐occurrence between whale sharks, baleen whales and tuna purse‐seine fisheries were mostly observed in productive areas during particular seasons. In light of the lack of a full coverage scientific observer on board program, the large, long‐term dataset obtained from logbooks of tuna purse‐seine vessels is highly important for identifying seasonal and spatial co‐occurrence between the distribution of fisheries and megafauna, and the underlying environmental variables. This study can help to design conservation management measures for megafauna species within the framework of spatial fishery management strategies.

Survival, Reproduction and Growth of the Marine Amphipod, Leptocheirus plumulosus, Following Laboratory Exposure to Copper-Spiked Sediment - Timothy J. Ward; Karin E. Gaertner; Joseph W. Gorsuch; Daniel J. Call (Bulletin of Environmental Contamination and Toxicology, 2015)

Survival and Growth of the Marine Polychaete, Neanthes arenaceodentata, Following Laboratory Exposure to Copper-Spiked Sediment - Timothy J. Ward; Karin E. Gaertner; Joseph W. Gorsuch; Daniel J. Call (Bulletin of Environmental Contamination and Toxicology, 2015)

Bycatch species composition over time by tuna purse-seine fishery in the eastern tropical Atlantic Ocean - Edgar Torres-Irineo; Monin Justin Amandè; Daniel Gaertner; Alicia Delgado de Molina; Hilario Murua; Pierre Chavance; Javier Ariz; Jon Ruiz; Nerea Lezama-Ochoa (Biodiversity and Conservation, 2014)

The behavioural dynamics of fishers: management implications - Silvia Salas; Daniel Gaertner (Fish and Fisheries, 2004)
In pursuing their livelihood, fishers develop strategies when faced with changes in regulations and other fishery conditions. Changes involve each individual in a decision‐making process governed by his/her own goals or constraints. Despite this reality, the complex dynamics of fishing has usually been ignored in designing management initiatives, which has contributed to management failures in many parts of the world. Fishers have generally been treated as fixed elements, with no consideration of individual attitudes based on their operating scales (geographical, ecological, social and economic) and personal goals. We review existing research on the social, economic and behavioural dynamics of fishing to provide insight into fisher behaviour and its implications for fisheries management. Emphasis is placed on fisher perception, and how fishers develop dynamic fishing tactics and strategies as an adaptive response to changes in resource abundance, environmental conditions and market or regulatory constraints. We conclude that knowledge of these dynamics is essential for effective management, and we discuss how such information can be collected, analysed and integrated into fisheries assessment and management. Particular emphasis is placed on small‐scale fisheries, but some examples from industrial fleets are provided to highlight similar issues in different types of fisheries.